Stretch could reduce hamstring injury risk during sprinting by right shifting the length- torque curve - Ruan, M.; Li, L.; Chen, C.; Wu, X. (The Journal of Strength and Conditioning Research, 2018)
It was hypothesized that static stretch would shift the length-torque curve to the right, which may reduce the risk of muscle strain injuries. The purpose of this study was to evaluate the acute effects of static stretching of hamstring (SSH) on the risk of hamstring injury during sprinting indicated by the shift of the length-torque relationship. Twelve female college athletes (age: 20.8 ± 0.7 years; height: 1.61 ± 0.05 m; body mass: 54.25 ± 4.22 kg) participated in this study. Subjects performed overground sprinting under 2 conditions: after warm-up with 4 × 30 seconds SSH or after warm-up without SSH. Three-dimensional kinematic and kinetic data and electromyography of biceps femoris long head (BFlh), rectus femoris, and vastus medialis were collected during testing. The maximum length of BFlh during late swing phase increased after SSH with large effect size and close to statistically significant (p = 0.05, d = 1.22), but the knee flexion torque at the peak length did not change significantly. Static stretching of hamstring significantly reduced peak values of both horizontal (d = 1.46) and vertical (d = 1.79) ground reaction forces, and BFlh's activation level during the preactivation (late swing) phase (p = 0.05, d = 2.16). The results indicated that the length of BFlh-knee torque relationship and the length of BFlh-hip torque relationships during the late swing phase and initial stance phase were shifted to the right after SSH, which may reduce risk of hamstring strain injuries. We suggest that preactivity static stretching should not be simply removed and participators should give priority to stretch muscles that are vulnerable to strain injuries.